Life and death under Stalin : Kalinin Province, 1945-1953 - Boterbloem, Kees, 1962- (McGill-Queen's University Press, 1999)
"Investigations of Stalin's regime have usually concentrated on events in Moscow, Leningrad, and other industrial centres of the Soviet Union. In contrast, Kees Boterbloem provides an unprecedented look at the lives of Russians in a typical, yet largely unnoticed, province. The result is a fascinating study of how the post-war Stalinist regime treated those in Kalinin province, from collective farmers and Communist Party members to Red Army veterans and labour camp prisoners."--Jacket